Prognostic value of human leukocyte antigen G expression in solid tumors: a systematic review and meta-analysis - Bartolome, Jorge; Molto, Consolacion; Benitez-Fuentes, Javier David; Fernandez-Hinojal, Gonzalo; Manzano, Aranzazu; Perez-Segura, Pedro; Mittal, Abhenil; Tamimi, Faris; Amir, Eitan; Ocana, Alberto (Frontiers in Immunology, 2023)
Introduction Identification of modulators of the immune response with inhibitory properties that could be susceptible for therapeutic intervention is a key goal in cancer research. An example is the human leukocyte antigen G (HLA-G), a nonclassical major histocompatibility complex (MHC) class I molecule, involved in cancer progression. Methods In this article we performed a systematic review and meta-analysis on the association between HLA-G expression and outcome in solid tumors. This study was performed in accordance with PRISMA guidelines and registered in PROSPERO. Results A total of 25 studies met the inclusion criteria. These studies comprised data from 4871 patients reporting overall survival (OS), and 961 patients, reporting disease free survival (DFS). HLA-G expression was associated with worse OS (HR 2.09, 95% CI = 1.67 to 2.63; P < .001), that was higher in gastric (HR = 3.40; 95% CI = 1.64 to 7.03), pancreatic (HR = 1.72; 95% CI = 0.79 to 3.74) and colorectal (HR = 1.55; 95% CI = 1.16 to 2.07) cancer. No significant differences were observed between the most commonly utilized antibody (4H84) and other methods of detection. HLA-G expression was associated with DFS which approached but did not meet statistical significance. Discussion In summary, we describe the first meta-analysis associating HLA-G expression and worse survival in a variety of solid tumors. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022311973.